Training face detector using adaboost algorithm - Chiu, Gary Kin Yung. (2009)
Face detection is a complex and challenging task due to the high variability in faces and amongst faces. Also for a given image, a face detector should be able to identify and locate all faces, regardless of their position, scale, orientation (up-right, rotated) and pose (frontal, profile). To reduce the complexity associated with this field, this project will focus on detecting upright frontal faces.